Правильное чтение новоперсидских слов в этимологическом словаре М. Фасмера - Ebrahimi Lialestani, Nahid (SlavVaria, 2024)
Correct reading of New Persian words in the etymological dictionary of M. Vasmer. The New Persian writing is based on the Arabic script. But in etymological dictionaries of the Russian language Persian examples are written in Latin letters. In scientific literature there are different systems of the socalled Romanization that can be divided into two groups: phonemic (transcription) and literal (transliteration). The report not only discusses their most important differences, but also draws attention to the benefits of knowing the details of Romanization referring to Max Vasmer’s dictionary examples. Vasmer mainly follows the phonemic principle, but there are many inconsistencies in the examples he cites.